Hubungan Ibu Perokok Pasif Selama Kehamilan Dengan Kejadian Infeksi Respiratori Akut Bagian Bawah - BRA I Ratu Windriya; Ismiranti Andarini; Endang Sahir (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Acute Respiratory Infection (ARI) has been the main cause of child morbidity and mortality, includes upper ARI and lower ARI. Lower respiratory infection is the infection under of larynx, includes epiglotitis, croup (laryngotracheobronchitis), bronchitis, bronchiolitis, and pneumonia. The one risk factor of lower ARI is air pollution (if in the house use firewood to cook and/or cohabit with active smoker). Prenatal exposure to cigarette smoke will affect the morphogenesis of fetus lung so it will increase respiratory infection risk after the fetus is born. This research aims to find out how big the relationship between maternal passive smoking during pregnancy with lower acute respiratory infection. Methods: The research was an analytical survey with case control approach implemented in March-April 2013 in RSUD Dr. Moewardi Surakarta. The samples was taken using purposive sampling and the number of samples based on rule of thumb. Dependent variable in this research was lower acute respiratory infection and independent variable was maternal passive smoking during pregnancy. The parents of the sample signed informed consent as the consent form and filled the questionnaire. Medical records was required for obtained the data about diagnose and nutrition status of the samples. This research were obtained 60 samples and analyzed use bivariate analysis continued multivariate analysis with logistic regression test. Results: The research with bivariate analysis showed that maternal passive smoking during pregnancy and low birth weight infant were significant with p < 0.05. Crude OR maternal passive smoking during pregnancy was 5.688. By multivariate analysis with logistic regression test obtained adjusted OR = 4.000, p = 0.043 (p < 0.05), and 95% CI = 1.043-15.343 for independent variable maternal passive smoking during pregnancy. Conclusions: There was significant relationship between maternal passive smoking during pregnancy with lower acute respiratory infection of child (p = 0.043), at the risk of 4.000 times more likely to suffer lower ARI. Keywords: Pregnant Maternal, Passive Smoking, Lower Acute Respiratory Infection